Contributions to three-dimensional Hardy-Hilbert-type integral inequalities - Christophe Chesneau (Hilbert Journal of Mathematical Analysis, 2025)
This article presents new extensions of the classical Hardy-Hilbert integral inequality involving primitive functions in three dimensions. Two complementary theorems are established, each providing a sharp upper bound for triple integrals associated with distinct kernel function structures. By introducing additional parameters, the proposed results offer greater flexibility and generality in the formulation and application of these inequalities.